Patient medication knowledge governing adherence to asthma pharmacotherapy: A survey in rural Lagos, Nigeria (2010)
Asthma is a chronic disease and often requires complex management. This study was undertaken in four pharmacies–V-Ninat Pharmacy, Videc Chemists, Tomabel Pharmacy and Josbet Chemists, all in Isolo, Lagos, to determine the level of adherence to the anti-asthmatic drugs by asthmatic patients who participated in the study. Data was collected using structured questionnaires administered to patients coming into the pharmacies. The questionnaire was administered during a one-on-one interview. Times of recruitment were varied in an attempt to avoid any bias or restriction of the sample in relation to gender, age, or employment status such as trading and teaching. There were 73 participants in the study. The participation rate was 67 (92%) of those individuals eligible. The mean age of participants was 57(± 17.7) years. 30 (45.2%) of respondents were males and 37 (54.8%) were females. The mean number of occasion of exercise per week was 28.26. Twenty six (26) (39.0%) of patients used “preventer” medication, that is medication that prevents asthmatic attack on those who frequently suffer from asthma, and 5 (7%) never used it. Participants offered a number of reasons explaining their non-adherence, the most common 24 (58.5%) were those who forgot to take “preventer” medication. Nine (9) (21.9%) were too busy, 5 (12.2%) were concerned about side effects and 3 (7.3%) did not believe it was effective. Other responses were offered only by individual participants and were not endorsed by the participant sample. Older patients adhered to their medication regimen more closely than younger patients. Fifty (50) (68%) patients used “preventer” medication and 17 (26%) patients used “reliever” that is, agent that relieves asthmatic attack on those who frequently suffer from asthma. Based on these findings and the result of hypothesis testing (p < 0.05), the study established poor medication knowledge, suboptimal device technique, and disturbing levels of patients adherence with management recommendations. Asthma education strategies need to be modified to engage patients with low asthma knowledge to achieve improved patient outcome. Further, strategies should be employed to motivate patients to use “preventer” medications during the times they feel well.